MENINGKATKAN KESADARAN KEWARGANEGARAAN PADA MASYARAKAT RUNGKUT DENGAN NILAI-NILAI PANCASILA - M, Ahmad Maulana; Saputra, Rangga Bagas (Cahaya Ilmu Bangsa Institute, 2024)
This study employs a qualitative approach to analyze the implementation of Pancasila values in enhancing citizenship awareness in the Rungkut community. By integrating participatory observation, in-depth interviews, and document analysis, the study gains a holistic understanding of how Pancasila values are interpreted and applied in the daily lives of the Rungkut community. Through active participation of the community, the study obtains authentic perspectives that help identify common patterns and factors influencing citizenship awareness. Utilizing thematic analysis, the study organizes various aspects of Pancasila values implementation, allowing for relevant conclusions to be drawn regarding the importance of these values in fostering citizenship awareness at the local level.